Australian Association for Exercise and Sports Science
Informationsangebot als Diashow zur Australischen Vereinigung für Sportwissenschaft The Australian Association for Exercise and Sports Science (AAESS) is a professional organisation which is committed to establishing, promoting and defending the career paths of tertiary trained exercise and sports science practitioners, who are in turn committed to best practice and client well-being. The central tenet of our profession is that: "Exercise and Sports Science is a multidisciplinary field concerned with the understanding and enhancement of human movement in the broadest sense, including general physical activity pursuits such as goal oriented fitness regimens and recreational sport as well as elite sport and the area of performance enhancement. It includes the knowledge, methods and applications of subdisciplines (ie. exercise physiology, biomechanics, motor control and motor development, exercise and sport psychology) as well as how they interact". AAESS was officially founded in 1991 to meet the professional needs of exercise and sports scientists in Australia. It is directed by an Executive Board comprised of leading academics and practitioners in these fields and is supported by a growing number of regional chapters throughout Australia.